Permeation of Biopolymers Across the Cell Membrane: A Computational Comparative Study on Polylactic Acid and Polyhydroxyalkanoate - Casalini, Tommaso; Rosolen, Amanda; Henriques, Carolina Yumi Hosoda; Perale, Giuseppe (Frontiers in Bioengineering and Biotechnology, 2020)
Polymeric nanoparticles, which by virtue of their size (1 – 1000 nm) are able to penetrate even into cells, are attracting increasing interest in the emerging field of nanomedicine, as devices for e.g. drugs or vaccines delivery. Because of the involved dimensional scale in the nanoparticle/cell membrane interactions, modeling approaches at molecular level are the natural choice in order to understand the impact of nanoparticle formulation on cellular uptake mechanisms. In this work, the passive permeation across cell membrane of oligomers made of two employed polymers in the biomedical field (poly-D,L-lactic acid (PDLA) and poly(3-hydroxydecanoate) (P3HD)) is investigated at fundamental atomic scale through molecular dynamics simulations. The free energy profile related to membrane crossing is computed adopting Umbrella Sampling. Passive permeation is also investigated using a coarse-grained model with MARTINI force field, adopting Well-Tempered Metadynamics. Simulation results showed that P3HD permeation is favored with respect to PDLA by virtue of its higher hydrophobicity. The free energy profiles obtained at full atomistic and coarse-grained scale are in good agreement each for P3HD, while only a qualitative agreement was obtained for PDLA. Results suggest that a reparameterization of non-bonded interactions of the adopted MARTINI beads for the oligomer is needed in order to obtain a better agreement with more accurate simulations at atomic scale.